Aerosol Test Chambers: Current State and Practice During the COVID-19 Pandemic - Yeh, Kenneth B.; Setser, Bradly (Frontiers in Bioengineering and Biotechnology, 2022)
Respiratory infectious disease outbreaks such as those caused by coronaviruses and influenza, necessitate the use of specialized aerosol test chambers to study aspects of these causative agents including detection, efficacy of countermeasures, and aerosol survivability. The anthrax attacks from 2001 and earlier biowarfare and biodefense also influenced the study of biological aerosols to learn about how certain pathogens transmit either naturally or through artificial means. Some high containment biological laboratories , which work with Risk Group 3 and 4 agents in biosafety level -3, biosafety level-4 containment, are equipped with aerosol test chambers to enable the study of high-risk organisms in aerosolized form. Consequently, the biomedical, military and environmental sectors have specific applications when studying bioaerosols which may overlap while being different. There are countless aerosol test chambers worldwide and this number along with numerous high containment biological laboratories underscores the need for technical standards, regulatory and dual-use compliance. Here we survey common aerosol test chambers and their history, current use, and practice. Our findings reinforce the importance and need for continued collaboration among the multi-disciplinary fields studying aerobiology and biological aerosols.